Why the debunking threat won’t go away - Kvandal, Halvor (International journal for philosophy of religion, 2023)
A central claim often made to debunk religious beliefs is that they would be formed regardless of whether they are true or false. One way to support this claim is to apply findings from the cognitive science of religion. However, this use of science in an argument against religious beliefs has been strongly criticized. This article is about weaknesses in that criticism. I consider two arguments. Firstly, the critic of debunking can argue that the debunker makes empirically dubious claims about the origin of religious beliefs. I argue that the debunker can avoid this problem because the controversial empirical claims are not necessary. General naturalistic assumptions about the origin of religion also create worries that support the central debunking claim. The second criticism focuses on the highly general nature of the claims or assumptions debunkers make about the origin of religious beliefs. Critics maintain that such claims or assumptions, even if true, fail to affect the specific religious beliefs you or I form. I respond, arguing that this criticism fails to engage with the most prominent version of debunking, which aims at classes of beliefs. Furthermore, by making a detour through a related discussion in metaethics, I show how this version of the debunking argument can be extended in such a fashion that it applies to a given individual who forms a religious belief.